Penyuluhan Pembuatan Puding Kulit Pisang Sebagai Solusi Zero-Waste Di Desa Pasi, Kabupaten Lamongan, Jawa Timur - Islami, Mega; Suryadi , Akmal; Zahirah , Jafni F.; Sa’idan , Gading Adian Kun (INCOME: Indonesian Journal of Community Service and Engagement, 2023)
The PKM team from UPN "Veteran" Jawa Timur carried out community service activities in Pasi village by conducting training on processing organic waste products. This activity aims to encourage the community to increase creativity and innovation as well as increase awareness about existing organic waste processing to create zero-waste. The counseling and training activities for making pudding from banana peels were attended by 30 people who are residents of Pasi Lamongan Village, East Java